First record of Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) in the state of Acre, Brazil - Adaime, Ricardo; Santos, Rodrigo Souza; Azevedo, Tatyane da Silva; Vasconcelos, Adriana da Silva; Sousa, Maria do Socorro Miranda de; Souza-Filho, Miguel Francisco (EntomoBrasilis, 2017)
Abstract. We report for the first time the presence of Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) in the state of Acre, Brazil, reared from guava fruit (Psidium guajava L.) and star fruit (Averrhoacarambola L.). This finding increases our knowledge about the geographical records of this fruit fly in the Brazilian Amazon. Primeiro registro de Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) no estado do Acre, Brasil Resumo. Registra-se pela primeira vez a presença de Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) no estado do Acre, Brasil, a partir de frutos de goiabeira (Psidium guajava L.) e de caramboleira (Averrhoacarambola L.), aumentando o conhecimento dos registros geográficos dessa mosca na Amazônia brasileira.